2005
DOI: 10.1097/01.bsd.0000138694.56012.ce
|View full text |Cite
|
Sign up to set email alerts
|

The Biomechanical Effects of Kyphoplasty on Treated and Adjacent Nontreated Vertebral Bodies

Abstract: It remains unclear whether adjacent vertebral body fractures are related to the natural progression of osteoporosis or if adjacent fractures are a consequence of augmentation with bone cement. Experimental or computational studies have not completely addressed the biomechanical effects of kyphoplasty on adjacent levels immediately following augmentation. This study presents a validated two-functional spinal unit (FSU) T12-L2 finite element model with a simulated kyphoplasty augmentation in L1 to predict stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
3
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 53 publications
0
58
3
1
Order By: Relevance
“…Although these findings may suggest that the risk of fracture is increased adjacent to an augmented vertebra, new fractures may be the result of the natural progression of osteoporosis. Indeed, some recent studies refute earlier findings, concluding that subsequent vertebral fractures are the result of excessive loading and not the augmentation process [1,23,51]. Therefore, due to the conflicting conclusions drawn by previous studies, the need still exists to determine the effect of cement augmentation on vertebral mechanics.…”
Section: Introductioncontrasting
confidence: 39%
See 2 more Smart Citations
“…Although these findings may suggest that the risk of fracture is increased adjacent to an augmented vertebra, new fractures may be the result of the natural progression of osteoporosis. Indeed, some recent studies refute earlier findings, concluding that subsequent vertebral fractures are the result of excessive loading and not the augmentation process [1,23,51]. Therefore, due to the conflicting conclusions drawn by previous studies, the need still exists to determine the effect of cement augmentation on vertebral mechanics.…”
Section: Introductioncontrasting
confidence: 39%
“…The mean endplate deformation for all specimens was 0.82 ± 0.025 mm at the maximum compressive load applied to the specimen, 1,620 ± 102 N. However, endplate deformation was not always equal between the caudal inferior and cranial superior endplate which abut a common disc (1) and high BV/TV and low endplate deformation (2) and thus be at risk of fracture following cement augmentation. Previous biomechanical in vitro tests [1,3,23] and finite element analyses [2,24,32,40,44,51] have reported conflicting results. The conflicting results between our experiment and previous finite element analyses may be attributed to differing injection volumes, loading parameters and inability to model the complex behavior of the intervertebral disc and 3D trabecular network.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, increased stiffness of the augmented segment is thought to increase the risk for adjacent-level VCF [1,30]. Another view put forward is that the clinically observed increased risk for adjacent-level fracture is likely due to an already weakened adjacent segment, as was the case causing the initial fracture to the treated segment, naturally caused by systemic bone disease (e.g., osteoporosis) [37]. Furthermore, a recent study has suggested that indeed adjacent-level VCF are more likely following cement augmentation if full fracture reduction is not achieved [32].…”
Section: Introductionmentioning
confidence: 99%
“…Finite element simulations have examined the efficacy of repair based on cement volume and distribution [12,17,23,30] at different levels of bone damage and osteoporosis [12,17,30], the importance of bone cement material properties [17], and alterations in the load transfer behavior between vertebrae in a motion segment [1,12,30,32,37]. Advances in imaging (e.g., micro-computed tomography, lCT) together with dramatic improvements in computational power have allowed for the development of high-resolution, anatomically accurate, large-scale microstructural FE models.…”
Section: Introductionmentioning
confidence: 99%